Effect of acupressure on depression, anxiety, stress, and sleep in nurses working in the COVID-19 ward - Masoumeh Ahmadi; Simin Jahani; Nasrin Elahi; Mohammad Hosein Haghighizadeh (Complementary Medicine Journal of Faculty of Nursing and Midwifery)
Introduction: Nurses are at a greater risk of contracting the coronavirus and experiencing psychological disorders due to their high contact with patients. This study was conducted with the aim of determining the effect of acupressure on depression, anxiety, stress, and sleep of nurses working in COVID-19 wards of teaching hospitals affiliated with Ahvaz Jundishapur University of Medical Sciences in 2022. Materials and methods: In this quasi-experimental study, nurses were randomly assigned to either the intervention (34 people) or control (33 people) group based on the inclusion criteria and after obtaining written consent. In the intervention group, the nurses were taught how to perform acupressure on the Shen Man point and Pericardium 6 (P6) of the hand, and they were asked to perform acupressure on the determined points twice a day for 4 weeks. Data collection tools included a demographic information form, the Depression Anxiety Stress Scale-21, and the Insomnia Severity Index. SPSS version 25 software and Mann-Whitney, Chi-square, t-test, and variance analysis with repeated measures were used for data analysis. Results: The mean scores of depression, anxiety, stress, and insomnia intensity were 12.63±4.30, 12.63±4.69, 14.73±2.51, 17.83±3.67, respectively, in the intervention group before the intervention, while they were 12.73±3.80, 12.50±5.68, 14.80±4.68, 17.26±3.89 in the control group. No statistically significant difference was observed between the two groups (P>0.05). Two weeks after the intervention, the mean values of depression, anxiety, stress, and insomnia severity were 11.67±4.19, 12.16±3.86, 10.50±2.51, 12.63±2.98, respectively, in the intervention group, whereas these values were 13.86±4.32, 13.60±4.88, 15.96±7.81, 16.18±3.15 in the control group. Four weeks after the intervention, these scores were 11.10±3.30, 11.00±2.91, 9.90±3.23, 11.96±2.84 in the intervention group, and 14.46±4.74, 13.46±2.91, 13.23±4.12, 18.50±2.63 in the control group, respectively. A statistically significant difference was observed between the two groups in terms of depression (P=0.005), stress (P=0.006), and insomnia intensity (P=0.0001). In terms of the anxiety variable (P=0.078) after the intervention, there was no statistically significant difference between the two groups. Conclusion: The findings of the present study showed that performing acupressure reduces stress, depression, and insomnia in nurses. Therefore, it is suggested that nursing managers teach acupressure skills in continuing education programs to help manage the psychological problems of nurses working in Coronavirus wards.